Pemberdayaan Masyarakat Melalui Bank Sampah di Desa Kerongkong Kecamatan Suralaga Kabupaten Lombok Timur - Rika Andriati Sukma Dewi; Muhammad Nursan; Fadli; Aeko Fria Utama FR; Deni Irawan (Universitas Mataram, 2022)
Waste management is still a serious problem that must be resolved, especially in Kerongkong Village, Suralaga District, East Lombok. One of the efforts that can be done is waste management through waste banks. Therefore, the purpose of this community service is to increase public knowledge regarding waste banks and improve community skills and income through waste bank management. This community service activity was carried out in Kerongkong Village, Suralaga District, East Lombok, which consisted of 2 activities including preparation and implementation of activities. The results of the service activities show that an increase in public knowledge about waste bank management and the establishment and empowerment program through a waste bank in Kerongkong Village, Suralaga District, East Lombok Regency has been able to reduce the amount of piles of waste generated by the community, improve community skills and income in managing waste banks. . To support the sustainability of the waste bank program, it is highly expected that there will be support from the community and the government so that the waste bank can maintain cleanliness and environmental sustainability in the future.